Life-cycle assessment of hydrogen production via catalytic gasification of wheat straw in the presence of straw derived biochar catalyst. (December 2021) - Loy, Adrian Chun Minh; Alhazmi, Hatem; Lock, Serene Sow Mun; Yiin, Chung Loong; Cheah, Kin Wai; Chin, Bridgid Lai Fui; How, Bing Shen; Yusup, Suzana
Graphical abstract: Highlights: The environmental impacts based on P5 unit are found to be negligible. P4 unit poses the highest environmental impact, especially on human health category. The whole process environmental impact is found to be 93.4017 mPt. "Wheat straw loading" parameter contributes the most to global warming potential. Straw biochar catalysts offer competitive H2 yield and lower environmental impact. Abstract: The environmental footprints of H2  production  via  catalytic gasification of wheat straw using straw-derived biochar catalysts were examined. The functional unit of 1 kg of H2  was adopted in the system boundaries, which includes 5 processes namely biomass collection and pre-treatment units (P1), biochar catalyst preparation using fast pyrolysis unit (P2), two-stage pyrolysis-gasification unit (P3), products separation unit (P4), and H2  distribution to downstream plants (P5). Based on the life-cycle assessment, the hot spots in this process were identified, the sequence was as follows: P4 > P2 > P1 > P3 > P5. The end-point impacts score for the process was found to be 93.4017 mPt. From benchmarking analysis, the proposed straw-derived biochar catalyst was capable of offering almost similar catalytic performance with other metal-based catalysts with a lower environmental impact.